The Influence of Organizational Capability on the Development of Village-Owned Enterprise Business Models - Arik Prasetya; Mukhamad Kholid Mawardi; Irfan Kharisma Putra; Ahmad Bachtiar Arif; Naufal Farras Alfattahu; Rama Virgil Elian (Program Pascasarjana Universitas Negeri Makassar, 2023)
One aspect of organizational resources is Human Resources (HR). Human resource development programs are very important in an organization to improve employee performance, because development can encourage the self-quality of existing employees. One of the variables that can be used in developing human resources is to understand Organizational Capability. Organization Capability is useful for developers of Village-Owned Enterprises (TVEs) can carry out their business processes well, so that TVEs can grow and develop. There are three things in understanding Organizational Capability, namely: Social Capital, Human Capital, and Intellectual Capital. Social Capital has a role in facilitating access to wider information sources and improving the quality, relevance and timeliness of information. Human Capital is defined as the knowledge, skills and abilities that reside with an individual and are utilized by the individual. Meanwhile, Intellectual Capital is conceptualized as knowledge to determine organizational capabilities. This type of research is explanatory with a quantitative approach. The research location was carried out at 9 TVEs in Wonosalam District, Jombang Regency with 32 TVEs administrators as respondents. The research results show that Intellectual Capital, Social Capital, and Human Capital have a significant simultaneous influence on the TVEs Business Model.